STRATEGI MENYENANGKAN DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR: TINJAUAN LITERATUR SISTEMATIS UNTUK MENGATASI KEBOSANAN SISWA - Yelvi Lestari; Syahrul Ramadhan; Urwatil Wustqo; Zahara Febriani; Zakiyatus Silmi; Susi Ratna Sari (STKIP Subang, 2026)
Social studies learning in elementary schools continues to face notable challenges, particularly low student engagement and high levels of boredom, often associated with the dominance of conventional teaching methods. This study aims to examine various enjoyable learning strategies and their contribution to improving student engagement and conceptual understanding. A qualitative approach was applied through a systematic literature review of 25 relevant sources, consisting of journal articles and proceedings published between 2020–2025. The findings show that five main strategies, joyful learning, game-based learning, traditional games, varied learning media, and active learning, consistently contribute to more engaging classroom experiences. These strategies not only help reduce boredom but also encourage active participation and foster deeper conceptual understanding. In addition, they support the creation of a more psychologically conducive learning environment. However, their implementation still faces several challenges, including limited facilities, teachers’ technical competencies, and classroom management complexity. Therefore, a flexible and context-based approach is needed. Overall, enjoyable learning strategies should be positioned as an essential component in enhancing the quality of social studies learning, making it more interactive, meaningful, and student-centered.